Effect of extra virgin olive oil on inflammatory markers and intestinal microbiota in chronic kidney disease patients. - Aliyah, Ruwiyatul; Taslim, Nurpudji Astuti (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction : The global prevalence of Chronic Kidney Disease (CKD) is 9.1%, with an increase of 29.3% from 1990 to 2018. A healthy diet with Extra Virgin Olive Oil (EVOO) consumption play a role in reducing inflammation and modulating gut microbiota in CKD patients. This study aims to assess the effect of extra virgin olive oil on immune system platelet-to-lymphocyte ratio (PLR) and Short Chain Fatty Acids (SCFA) in patients with Chronic Kidney Disease (CKD). Methods: Randomized clinical trial at Dr. Wahidin Sudirohusodo Hospital Makassar on December 2022. The total sample was 30 and divided by two groups , each group both intervention with EVOO 40 ml / day and control group with normal diet (15 patients ). Data were collected through questionnaires and direct measurements for anthropometric (Body weight and Body height). Energy intake with twenty four hours recall. platelet-to-lymphocyte ratio (PLR) through routine blood test and Short chan fatty acids (SCFA) through Pro Healthy Gut tests. Data were analyzed using SPSS version 26 with t-test analysis. Results: EVOO administration had a significant result on inflammatory markers and gut microbiota. The intervention group had increased energy composition (1370.63±147.76 to 1690.63±147.76; p=0.000) and fat (19.93±7.25 to 57.93±7.25; p=0.000), accompanied by a decrease in Platelet-Lymphocyte Ratio (PLR) (210.76±80.20 to 169.89±54.22; p=0.026) and an increase in Short Chain Fatty Acids (SCFA) in feces (6.86±4.42 to 16.98±15.47; p=0.021) . While the control group showed no significant changes. Conclusion: Extra virgin olive oil (EVOO) had no significant effect on the nutritional status of patients with Chronic Kidney Disease (CKD) , but reduced inflammation (decreased PLR). In addition improved gut microbiota health (increased SCFA).